A study on the symptom profile of depressive disorder in elderly Turkish patients: A factor analysis study (Annals of Medical Research, 2021)
Aim: Depressive disorder manifests itself differently in elderly patients due to the symptom profile. We conducted this study on a population of elderly major depressive disorder patients in Turkey with the aim of determining the sociodemographic characteristics, distribution, and associations of their symptoms.Material and Method: A retrospective study of 137 patients hospitalized during the last ten years in the Geropsychiatric Clinic of the Department of Psychiatry, Cerrahpaşa School of Medicine, Istanbul University. The patients were diagnosed according to the DSM IV criteria.Results: Majority (51.8%) of the patients were female, most of which were married (65%). The most common symptoms in elderly patients in order of frequency were distress 112 (81.8%) anxiety 97 (70.8%), and insomnia 96 (70.1%). The least frequently observed symptoms were disorientation 5 (3.6%), nihilistic delusions 5 (3.6%), and increased appetite 2 (2.2%). The symptoms clustered in accordance with the DSM IV system.Conclusion: It was concluded that the sociodemographic characteristics and weighted distribution of symptoms in Turkish geriatric depression patients were closely in parallel with the existing literature. However, results indicate a need to repeat this study in order to explore the same in a general Turkish population.Keywords: Elderly; depression; sign; symptom; factor analysis.
Keywords: key with the aim of determining the sociodemographic characteristics, distribution, and associations of their symptoms.br /Material and Method: A retrospective study of 137 patients hospitalized during the last ten years in the Geropsychiatric Clinic of the Department of Psychiatry, Cerrahpaşa School of Medicine, Istanbul University. The patients were diagnosed according to the DSM IV criteria.br /Results: Majority (51.8%) of the patients were female, most of which were married (65%). The most common symptoms in elderly patients in order of frequency were distress 112 (81.8%) anxiety 97 (70.8%), and insomnia 96 (70.1%). The least frequently observed symptoms were disorientation 5 (3.6%), nihilistic delusions 5 (3.6%), and increased appetite 2 (2.2%). The symptoms clustered in accordance with the DSM IV system.br /Conclusion: It was concluded that the sociodemographic characteristics and weighted distribution of symptoms in Turkish geriatric depression patients were closely in parallel with the existing literature. However, results indicate a need to repeat this study in order to explore the same in a general Turkish population.br / Elderly; depression; sign; symptom; factor analysis.